Chemistry a course for 'O' level (third edition) - Prescott, Christopher N. (Marshall Cavendish Education; Singapore, 2000)
"Chemistry for Cambridge 'O' Level" provides a clear and concise guide to key chemistry concepts, offering students a solid foundation in theory and practical applications to excel in their O-Level exams.